2015
DOI: 10.1515/ijamh-2014-0045
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged rooming-in in infancy is associated with generalized anxiety disorder in the adolescent period

Abstract: Sleeping in the same room with children for a long time may result in anxiety disorders in later period due to possible difficulties in bonding and/or less self-confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Other studies exploring the effect of bed-sharing on the child behavior and mental health were found at the literature (Madansky and Edelbrock, 1990, Okami et al, 2002, Barajas et al, 2011, Kaymaz et al, 2014). In a randomly selected community sample of 2 year-old children (n =199) and followed-up within 2 weeks of the 3rd anniversary, the majority of parents reported that their child had slept in their bed with them at least once during the previous two months (11% reported that the child always co-slept) (Madansky and Edelbrock, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies exploring the effect of bed-sharing on the child behavior and mental health were found at the literature (Madansky and Edelbrock, 1990, Okami et al, 2002, Barajas et al, 2011, Kaymaz et al, 2014). In a randomly selected community sample of 2 year-old children (n =199) and followed-up within 2 weeks of the 3rd anniversary, the majority of parents reported that their child had slept in their bed with them at least once during the previous two months (11% reported that the child always co-slept) (Madansky and Edelbrock, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In a small case-control study planned to investigate whether anxiety disorders in adolescents have a link with the separation time of bed/bedroom sharing with parents, Kaimaz et al (Kaymaz et al, 2014) recruited 51 adolescents who were diagnosed as generalized anxiety disorder with no-comorbidity and 71 healthy adolescents as the control group, who were chosen randomly. Mean duration of bed-sharing in the case group was longer than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adopted conceptualizations insofar, viewed cosleeping as a sleeping arrangement where the child slept either with both parents or with the mother (e.g., Kaymaz et al, 2014;Keller & Goldberg, 2004;Santos et al, 2017;Teti & Crosby, 2012), apparently adhering to the attachment tradition (Ainsworth, Blehar, Waters, & Wall, 1978;Bowlby, 1982;Cassidy & Shaver, 2010). However, as Ross, Hinshaw, and Murdock (2016) pointed out, attachment theory "may be overlooking the role of a second parent in psychological well-being" (p. 400), thereby a co-sleeping conceptualization from an attachment standpoint is limited in its dyadic focus and neglectful of triadic-level interrelationships.…”
Section: Embedding Co-sleeping Within Family Systems Theorymentioning
confidence: 99%